Turnover intention and its antecedents: The mediating role of work–life balance and the moderating role of job opportunity - Ahmad Saufi, Roselina; Aidara, Samsidine; Che Nawi, Noorshella Binti; Permarupan, P. Yukthamarani; Zainol, Noor Raihani Binti; Kakar, Abdul Samad (Frontiers in Psychology, 2023)
It is challenging for academic institutions to attract and retain top talent as academic attrition in higher education is increasing. The human resource (HR) environment has changed due to lifestyle adjustments. The new role of HR involves establishing values, mechanisms for achieving work–life balance (WLB), and effective retention strategies. The primary area of discussion among business executives and HR professionals is how exceptional academic industry talent can be retained and maintained. Thus, the study objective is to investigate the relationship between academic HR strategy (HRS) and sustaining WLB with the moderating role of external job opportunity (JBO). The theoretical study foundation was the theory of planned behaviour and social exchange theory. Data from 466 respondents was collected using a cross-sectional research approach via an online survey and analysed using partial least square structural equation modelling. The outcome of the study showed that organisation reputation and occupational prestige significantly influence employee intention to leave. The findings also demonstrated that sustaining WLB significantly mediated the relationship between a dynamic HRS and an employee’s intention to leave. The results confirmed that JBO significantly moderated the relationship between sustaining WLB practice and the intention to leave. The results presented a comprehensive retention strategy model that can greatly assist the HR industry, policymakers, and education management in developing an effective strategic recruitment and retention plan.